DESIGN AND DEVELOPMENT OF COMPUTER-BASED TEST (CBT) SYSTEM IN THE ACADEMIC SELECTION PROCESS FOR RECRUITING SOLDIERS IN THE AIR FORCE - Anggraini Pratiwi, Nabilla; Iskandar, Dadang; Nofiyati, Nofiyati (Jurnal Teknik Informatika (Jutif), 2024)
The selection of recruits is a crucial stage for the continuity of the existence of the Indonesian Air Force (TNI AU). This selection process consists of several stages, one of which is the academic stage conducted with a paper-based test model. This model requires a lengthy conventional process, indicating the need for a computer-based system to expedite the selection process. Therefore, this study proposes a solution for the academic selection of TNI AU recruits by implementing a Computer Based Test (CBT) system, aiming to enhance the efficiency of the selection process. The development of the CBT system utilizes the Waterfall method, with PHP programming language and MySQL. The research results in a CBT system designed for electronic academic selection of TNI AU recruits, equipped with Safe Exam Browser (SEB) to reduce cheating during the selection exams. According to testing results, the CBT system meets the requirements and is deemed suitable for use.